Designing, In-Silico Based Virtual Screening, Synthesis, Biological Evaluation and Molecular Dynamics Simulation of Novel Pyrazoleanalogs for the Treatment of Malaria - Thakur, Aman; Paliwal, Deepika; Kumar, Ajay; Aggarwal, Shilpy (Letters in Organic Chemistry, 2025)
Malaria, possibly a life-threatening disease, primarily affects the African and South Asian populations worldwide. The development of resistance to current treatment regimens for malaria is a major concern among the medical fraternity. This leads to the need to discover novel antimalarial agents that can attenuate the resistant malarial parasite. To discover novel pyrazole-based molecules that can be used to cure malaria. Initially, a 2D-QSAR-based virtual screening of the 16 pyrazole-based molecules designed for malaria was performed. Further virtual screening was conducted through the molecular docking simulations. Based on the results of the QSAR and molecular docking-based screening, hit compounds were synthesized and evaluated <span class=
Keywords: virtual screening